2016
DOI: 10.1007/s12079-016-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the oxytocin-oxytocin receptor signaling network

Abstract: Oxytocin, a nine amino acid long neuropeptide hormone, is synthesized in the hypothalamus and stored and released from the neural lobe of the pituitary gland. Although commonly known for its central role in the regulation of parturition and lactation, oxytocin signaling also plays a key role in modulating social behavior, evoking contentment, initiating maternal behavior, inducing trust, generosity and bonding in humans and animals. Oxytocin signaling can prove to be of great importance in therapeutics and dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 36 publications
(36 reference statements)
0
35
0
1
Order By: Relevance
“…Therefore, our results implied that OT/OTR may be involved in the activation of the ERK1/2 signaling pathway, consequently affecting the glandular contraction and musk secretion. In addition, nuclear ERK1/2 was considered to regulate cell proliferation by inducing c-fos expression 13 , 14 . Our previous study demonstrated that in the breeding season, the number of epithelial cells and glandular cells in the scented gland markedly increased, suggesting a seasonal change in cell proliferation 23 , 26 , 27 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results implied that OT/OTR may be involved in the activation of the ERK1/2 signaling pathway, consequently affecting the glandular contraction and musk secretion. In addition, nuclear ERK1/2 was considered to regulate cell proliferation by inducing c-fos expression 13 , 14 . Our previous study demonstrated that in the breeding season, the number of epithelial cells and glandular cells in the scented gland markedly increased, suggesting a seasonal change in cell proliferation 23 , 26 , 27 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological outcomes associated with OT activation are known to be involved in neuronal membrane/cell excitability (Gong et al 2015), long-term potentiation (Lin et al 2012) and regulating many facets of social behavior (Blume et al 2008;Jurek et al 2012;Wang et al 2015). For a full representation of the OT signaling network see Chatterjee et al (2016) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 es.…”
Section: Figurementioning
confidence: 99%
“…Recently, an ambitious synthesis of previous reports of OXTR intracellular signaling pathways was completed by Chatterjee and colleagues. To date, this open-source resource on NetPath is the most comprehensive overview of the OXTR signaling cascade (Chatterjee et al, 2016). Several of the more well-established pathways and their functional role at the cellular level will be described below.…”
Section: Signaling and Cellular Functionmentioning
confidence: 99%